Synergistic mechanisms of DGAT and PDAT in shaping triacylglycerol diversity: evolutionary insights and metabolic engineering strategies - Cai, Wen-Lu; Yu, Shui-Yan; Hu, Yong-Hong (Frontiers in Plant Science, 2025)
Triacylglycerol (TAG), the primary storage lipid in plants, determines oil quality through its fatty acid composition. This review focuses on the biosynthesis of TAG, systematically analyzing the mechanistic similarities and differences between the acyl-CoA-dependent Kennedy pathway (catalyzed by the rate-limiting enzyme DGAT) and the acyl-CoA-independent pathway (regulated by the rate-limiting enzyme PDAT). By integrating functional studies, evolutionary analyses, and lipidomic data, we reveal the distinct substrate preferences of DGAT and PDAT, their differential contributions to TAG synthesis, and their synergistic mechanisms in shaping triacylglycerol diversity. This work establishes a theoretical framework for the targeted engineering of plant oils with enhanced nutritional and industrial value through optimized fatty acid profiles.